Finance and the Macroeconomic Process in a Classical Growth and Cycles Model - Jamee K. Moudud (Levy Economics Institute of Bard College, 1998)
The aim of this paper is to derive an endogenous growth and cycles model that integrates sectoral incomes, expenditures, and finance requirements into an ex ante social accounting matrix (SAM) in the spirit of the Cambridge Economic Policy Group. The SAM includes households, businesses, a banking sector with non-zero net worth, and the government. Investment in circulating capital, endogenous bank credit to finance accumulation, and the negative feedback effect of debt on investment are at the core of the short-run cyclical dynamics. The business cycle dynamics are described by the dual disequilibria relationship that relates monetary and goods market disequilibria to each other. Market disequilibria result from the discrepancy between ex ante plans and expectations and ex post outcomes. The short-run cycle in the model is the 3-5 year inventory cycle in which aggregate demand and supply chase each other ceaselessly in order to reach equilibrium. Firms respond to excess demand by lowering inventory stocks and increasing investment in circulating capital, which expands output via the Léontief input-output relationship. Over the medium run, they respond to imbalances between actual and normal capacity by increasing fixed capital investment. Over the medium to long run, the path of accumulation is internally financed and regulated by the rate of profit. One can conclude that the macrodynamic model is a synthesis of the Physiocrats' "circular flow" approach to modeling the economy and the endogenous growth perspective of some classical economists, von Neumann, and Harrod. Finally, the endogenous cyclical dynamics are very much in the spirit of Kalecki and Minsky.
Keywords: 330